PROBLEMATIKA PENDIDIKAN MADRASAH DALAM PEMBAHARUAN PENDIDIKAN ISLAM DI INDONESIA - rahimi rahimi rahimi (Jurnal Al-Fatih, 2021)
ABSTRACT The history of Islamic education in Indonesia has been started in the early XX century AD until today it is quite a long journey. Where quite drastic developments occurred during the old order and continued to develop during the new order. As an educational institution, madrasas are institutions that grow and develop by and from society, as well as for societies that are full of Islamic cultural meanings, whether they are recognized or not, madrasas have traveled a long journey of civilization in realizing the formation of a national personality which is full of changes, however madrasas are reluctant to let go of their original meaning in accordance with their cultural ties, namely Islamic culture. Key Word: Madrasah, Renewal, Islamic Education